The Effectiveness of BUMKal Oerip Soemohardjo in Community Economic Empowerment - Karan Arya Kusuma; Mei Maemunah (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2026)
This study aims to analyze the effectiveness of the Village-Owned Enterprise (BUMKal) Oerip Soemohardjo program in economically empowering the community of Sardonoharjo Village, Ngaglik District, Sleman Regency. The urgency of this research lies in the expectation that BUMKal will serve as a driving force for rural economies following the enactment of the Village Law, as well as the phenomenon of BUMKal revival after the COVID-19 pandemic, during which many failed. The method used is descriptive qualitative research employing observation, in-depth interviews, and documentation. Data analysis followed the Miles and Huberman model, integrated with Indrajit’s (2016) effectiveness theory across three dimensions (support, capacity, value) and Bressers’ (2004) Contextual Interaction Theory. The results indicate that program effectiveness is at a moderate-to-high level. The support dimension is strong due to the existence of Village Regulations, capital allocation of IDR 250 million, and market protection. The capacity dimension is innovative, with homecare, brokerage, and tourism units, but remains weak in digitalization. The value dimension is perceived by the community through an increase in MSME turnover of up to 150%, access to affordable services, and the creation of new jobs. This study recommends enhancing business unit digitalization, expanding community participation, and strengthening human resource capacity.